Keynes and after - "Stewart, Michael" (New York, 1983)
In 1936 Keynes published "The General Theory of Employment, Interest and Money". Why was it so important? What did it say? How did it change things? Did the answer it provided to unemployment make inflation inevitable? Has Keynesianism been superseded by monetarism? How far do economic policies influence unemployment levels? These issues are discussed in this introduction to Keynes' work and ideas.
Keywords: Keynesian economics